2020
DOI: 10.1016/j.bbi.2020.05.076
|View full text |Cite
|
Sign up to set email alerts
|

Gestational poly(I:C) attenuates, not exacerbates, the behavioral, cytokine and mTOR changes caused by isolation rearing in a rat ‘dual-hit’ model for neurodevelopmental disorders

Abstract: Many psychiatric illnesses have a multifactorial etiology involving genetic and environmental risk factors that trigger persistent neurodevelopmental impairments. Several risk factors have been individually replicated in rodents, to understand disease mechanisms and evaluate novel treatments, particularly for poorly-managed negative and cognitive symptoms. However, the complex interplay between various factors remains unclear.Rodent dual-hit neurodevelopmental models offer vital opportunities to examine this a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 161 publications
(222 reference statements)
2
29
0
Order By: Relevance
“…Different behavioral and morphofunctional brain abnormalities in offspring of poly (I:C)-treated dams have been observed after puberty ( Zuckerman et al, 2003 ; Ozawa et al, 2006 ; Meyer and Feldon, 2012 ; Meyer, 2014 ; Luchicchi et al, 2016 ). In concordance with findings in brain of subjects with schizophrenia, previous works confirmed that this MIA model promotes the accumulation of pro-inflammatory mediators such as different cytokines, as well as intracellular inflammatory and oxido/nitrosative mediators such as the transcription factor NFkB or the inducible nitric oxide synthase (iNOS) ( Song et al, 2011 ; Volk et al, 2015 ; MacDowell et al, 2017 ; Goh et al, 2020 ). All these abnormalities suggest that MIA induced by poly (I:C) promotes in offspring a face-valid schizophrenia-like model.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…Different behavioral and morphofunctional brain abnormalities in offspring of poly (I:C)-treated dams have been observed after puberty ( Zuckerman et al, 2003 ; Ozawa et al, 2006 ; Meyer and Feldon, 2012 ; Meyer, 2014 ; Luchicchi et al, 2016 ). In concordance with findings in brain of subjects with schizophrenia, previous works confirmed that this MIA model promotes the accumulation of pro-inflammatory mediators such as different cytokines, as well as intracellular inflammatory and oxido/nitrosative mediators such as the transcription factor NFkB or the inducible nitric oxide synthase (iNOS) ( Song et al, 2011 ; Volk et al, 2015 ; MacDowell et al, 2017 ; Goh et al, 2020 ). All these abnormalities suggest that MIA induced by poly (I:C) promotes in offspring a face-valid schizophrenia-like model.…”
Section: Introductionsupporting
confidence: 82%
“…Likewise, a decrease in the rat brain cortical 5-HT content was observed in the offspring born from bacterial toxin lipopolysaccharide-immune-challenged mothers ( Swanepoel et al, 2018 ). However, there are also studies reporting unaltered tissue 5-HT concentrations in the FC of MIA animal models ( Winter et al, 2009 ; Abazyan et al, 2010 ; Hadar et al, 2015 ; Goh et al, 2020 ). The discrepancies highlight the importance of the intensity of MIA, as evidenced by the dose of immunogenic substance used, as well as the impact on the neurodevelopmental trajectory in relation to gestation time for the MIA.…”
Section: Discussionmentioning
confidence: 99%
“…Although the consensus is that schizophrenia begins with hypofunction of NMDA receptors on GABAergic interneurons leading to disinhibition of pyramidal cells and excitotoxic damage to CA1 [75], MRS generally shows little hippocampal change in early schizophrenia [76]. Our NOD studies began at the accepted onset of adulthood, which is approximately 3 weeks after typical emergence of isolation-induced dopaminergic changes and hyperlocomotion [77]. Since our microsensor studies continued for almost 3 months after this first emergence it can be argued that current findings more closely mirror chronic disease where MRS can reveal decreased glutamate in patients [19], potentially due to reduced synaptic density [20] and VGLUT1 expression [21,22].…”
Section: Discussionmentioning
confidence: 96%
“…Specifically, single housing following prolonged EE exposure was associated with increased weight gain, elevated helplessness and passive coping behaviors, and blunted hypothalamic-pituitary-adrenocortical activity (Morano et al, 2019; Smith et al, 2017). In contrast, isolation rearing following MIA in SD-housed animals was protective against negative impacts on behavior and neurophysiology (Goh et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, a mid-gestational injection of polyinosinic:polycytidylic acid (poly (I:C)), a viral mimetic toll-like receptor 3 agonist, can induce an extensive collection of innate immune responses (Mueller et al, 2019) and lead to a wide array of abnormalities in neurophysiology, behavior and cognitive abilities (see (Haddad et al, 2020) for review). Whereas the vast majority of previous studies have addressed the adverse effects of MIA, prior research has also revealed that MIA-treated offspring can exhibit improvements in cognitive functioning (Makinson et al, 2019; Nakamura et al, 2021), blunted responses to a second immune challenge in adolescence (Clark et al, 2019), and a higher level of resilience to the disruptive effects of isolation rearing on behavior and neurophysiology (Goh et al, 2020). Recently, it has been shown that poly (I:C)-induced MIA at a specific window of parvalbumin interneuron development can lead to improvements in spatial working memory (Nakamura et al, 2021).…”
Section: Introductionmentioning
confidence: 99%